Mechanism of the Housing Market Functioning - Maciejasz-Świątkiewicz, Marta (Mechanizm funkcjonowania rynku mieszkaniowego, 2010)
Real estate market is quite specific because of the features of the object of trade. It works differently from other markets, especially considering time effects. It needs some external support because in short term changes are hardly seen. There is a place for government activity here. Housing and real market policy is connected with giving some financial and administrative support for market participants. This activity influences the way people behave. However, people's behaviour is determined by many other elements. Thus, the public authorities should not omit these psychological and sometimes social determinants of the way people make decisions on the real estate market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 125, s. 144-151
Keywords: housing market; real estate market; housing policy; determinants of behaviour